Redactamos un texto - Pelaez Hurtado, Yolanda (2019)
This lesson plan entitled "We write a descriptive text" is designed for the second grade of Primary Education and was developed in the area of Communication taking into account the Communicative approach. The present work is structured in three parts: The first part contains the Introduction that is aimed at class planning, performance that is taken into account, evidence of learning and the assessment instrument to be used In the second part, the Theoretical Support referred to the conceptual variables of the topic to be treated is developed, with the determination to explain what is presented in the present work in a simple, clear way and with a theoretical base that supports it. _x000D_ Finally, the third part is located to the Pedagogical Support, the foundation of the Area, the profile of progress that the student must achieve when completing the Regular Basic Education, the Didactic and Cognitive Processes and the approaches that guide the Area in reference. In addition to evaluation techniques and instruments